Anti-diabetic Activity of Dry Extract of Gymnema Sylvestre - Sanna Sboeva (Journal of Global Pharma Technology, 2020)
The purpose of the study was to study the mechanism of antidiabetic action and compare the hypoglycemic effect of taking extracts of different concentrations of gurmar in a laboratory rat population. Studies were conducted in 2018 in a population of 400 laboratory rats based on the Federal State Autonomous Educational Institution of Higher Education I.M. Sechenov First Moscow State Medical University of the Ministry of Health of the Russian Federation (Sechenov University) (Moscow, Russian Federation). 300 animals made up the experimental group, 100 - the control. We used 25, 50, and 75% gurmar extract and diabeton, which were given orally to animals from the experimental group at a dosage of 70 mg to 1100 mg per 1 kg of body weight and 10 mg per 1 kg of body weight, respectively. Tests for glucose digestibility were performed by administering extracts of gurmar after fasting, dosage of 270 mg per 1 kg of body weight. The hypoglycemic effect of gurmar-based drugs activates enzymes associated with the inhibition of absorption of glucose from the intestine, as well as with its breakdown. Studies have established 25% as the most optimal dose of gurmar extract. The dosage in this case is 270 mcg per 1 kg of body weight. The maximum hypoglycemic effect is observed 2 hours after taking the drug. For high concentrations of the drug, a 25–30% lower hypoglycemic activity was recorded. Another drug, taken for comparison-diabeton, is superior in its effect to 25% gurmar extract by 20%. A 30% increase in beta-endocrinocyte nuclei may indicate an increased physiological activity of these cells.Keywords: Gurmar, type 2 diabetes mellitus, Extracts, Diabeton.